KAJIAN ESTETIKA DESAIN UANG KERTAS SERIBU RUPIAH TAHUN 1980 KARYA SUDIRNO DEL - Sucihati, Wiwin Trisning Kasih (Acintya, 2023)
This study aims to find out the idea of creation, to describe the symbolic meaning, and to find out the aesthetics of the visual form of the RP.1,000 banknote by Sudirno Del. This study uses a qualitative descriptive. The sampling technique using purposive sampling and snowball sampling. Research data collection was carried out by interview, observation, and documentation techniques. This study uses a Flow Model of Analysis. The results of the study are as follows, (1) The idea of creating a design for the banknotes began with a process of contemplating the identity of the cultural history of the Indonesian nation. Sudirno Del was inspired to choose ideas about the natural beauty that exists in Indonesia. Influenced by the psychological factor of longing for his hometown, and also a sense of admiration for the beauty of the Canyon Cliffs Sianok which is felt to represent the beauty of Indonesia. The chosen hero Dr. Soetomo, related Sudirno's personal experience. Related to the services of the movement's figures, Dr. Soetomo is a figure engaged in organizations for people's welfare in the fields of education, health and agriculture. (2) The design of the banknotes functions as a medium that accompanies messages through icons, indexes, and symbols to remember and honor the services of heroes, as well as displaying the beauty of the natural landscape in Indonesia so that it can be seen by the people of Indonesia and the world. (3) The design on the banknotes contain aesthetic value based on the successful fulfillme